Thermal safety coating diaphragm as well as preparation method and application thereof

By using a multi-layer coating structure composed of inorganic solid electrolyte and phase change material on the lithium-ion battery separator, the problem of thermal runaway and combustion explosion of lithium-ion batteries at high temperatures is solved, extending the thermal runaway time and improving the safety of the battery Performance and ionic conductivity.

CN119315218AActive Publication Date: 2025-01-14JINLONGYU NEW ENERGY (SHENZHEN) CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411369042.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-09-24
Filing Date
2024-09-29
Publication Date
2025-01-14
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

Existing lithium-ion battery separators are prone to thermal runaway and combustion explosion at high temperatures. Existing surface-coated inorganic materials are difficult to effectively reduce the temperature rise rate, resulting in insufficient battery safety.

Method used

Using a multi-layer coating structure composed of inorganic solid electrolytes and phase change materials, the mass proportion of phase change materials is regulated, the surface layer contains a large amount of phase change materials to quickly absorb heat, and the bottom layer contains a small amount of phase change materials to inhibit the heat shrinkage of the diaphragm matrix, and synergistically It reduces the temperature rise rate of thermal runaway and increases ionic conductivity.

Benefits of technology

Effectively extend the time of thermal runaway, improve the safety performance of the battery, and give the diaphragm a good ionic conductivity, reduce heat diffusing to the diaphragm matrix, and reduce the risk of sharp temperature rise.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005067066110000071
    Figure BDA0005067066110000071
  • Figure BDA0005067066110000081
    Figure BDA0005067066110000081
Patent Text Reader

Abstract

The invention relates to a thermal safety coating diaphragm as well as a preparation method and application thereof, and belongs to the technical field of methods or devices for directly converting chemical energy into electric energy. The thermal safety coating diaphragm comprises a diaphragm base body and a coating arranged on at least one side surface of the diaphragm base body, the coating comprises a bottom layer in contact with the diaphragm substrate and a surface layer covering the bottom layer; the bottom layer and the surface layer are mainly composed of an inorganic solid electrolyte and a phase change material, and the mass ratio of the phase change material in the bottom layer is smaller than the mass ratio of the phase change material in the surface layer. The thermal safety coating diaphragm not only can maintain relatively high ionic conductivity, but also can effectively delay the thermal runaway time, so that the safety of the battery is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of methods or devices for directly converting chemical energy into electrical energy, and in particular to a thermally safe coated diaphragm and a preparation method and application thereof. Background Art

[0002] As one of the key components of lithium-ion batteries, the diaphragm has the function of isolating the positive and negative electrodes in the battery to prevent short circuits and providing a transmission channel for lithium ions. The performance of the diaphragm plays a key role in the interface structure, battery capacity and cycle performance of the battery, especially in the safety of the battery. At present, the lithium-ion battery diaphragm is mainly polyolefin diaphragm (such as polyethylene diaphragm or polypropylene diaphragm), but the heat resistance of polyolefin diaphragm is general, and the polyolefin microporous diaphragm will shrink at around 100°C; when the temperature rises to 130-150°C, the polyolefin diaphragm will also cause closed pores, thereby blocking the transmission path of lithium ions and causing battery failure. At the same time, since the temperature difference between the melting destruction temperature of the polyolefin diaphragm and its closed pore temperature is small (for example, the closed pore temperature of the PE diaphragm is about 130°C, and its melting destruction temperature is about 140°C), the residual heat generated after the closed pore will still cause the temperature of the diaphragm to continue to rise, which is easy to cause the diaphragm to melt and cause accidents. To address this problem, existing polyolefin separators are mainly modified by coating inorganic materials (such as alumina, boehmite, etc.) on the surface, so that after the separator reaches the softening temperature of the polyolefin, it can still maintain its original shape to prevent short circuits, thereby improving the safety of the battery. However, in actual applications, it is found that the method of simply coating the surface of the polyolefin separator with inorganic materials can improve the thermal stability of the separator to prevent thermal runaway, but it is difficult to effectively reduce the rate of temperature rise when thermal runaway occurs, causing the temperature of the battery cell to rise sharply in a very short period of time and become out of control, or even burn and explode. Summary of the invention

[0003] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a thermal safety coated diaphragm and a preparation method and application thereof.

[0004] To achieve the above object, the technical solution adopted by the present invention is:

[0005] In a first aspect, the present invention provides a thermal safety coated diaphragm, which comprises a diaphragm substrate and a coating arranged on the surface of at least one side of the diaphragm substrate; the coating comprises a bottom layer in contact with the diaphragm substrate and a surface layer covering the bottom layer; the bottom layer and the surface layer are both mainly composed of an inorganic solid electrolyte and a phase change material, and the mass proportion of the phase change material in the bottom layer is less than its mass proportion in the surface layer.

[0006] The present invention uses a bottom layer and a surface layer mainly composed of an inorganic solid electrolyte and a phase change material as the coating of the diaphragm to form a thermally safe coated diaphragm, and regulates the mass proportion of the phase change material in the bottom layer and the surface layer, so that when the battery cell has thermal runaway, the surface layer close to the electrode side and containing a large amount of phase change material quickly absorbs the heat diffused from the runaway point (heat source), so as to reduce and slow down the diffusion of heat to the diaphragm matrix, and effectively alleviate the side reactions and decomposition of the electrolyte and auxiliary materials; while the bottom layer in contact with the diaphragm matrix and containing a small amount of phase change material can use the inorganic solid electrolyte with good heat resistance to fully inhibit the thermal shrinkage of the diaphragm matrix, and use a small amount of phase change material to further absorb the heat transferred from the surface layer, so that the bottom layer and the surface layer work together to reduce the temperature rise rate from T1 (thermal instability temperature, starting point of self-heat generation) to T2 (thermal runaway trigger temperature), prolong the thermal runaway time, and improve the safety performance of the battery; at the same time, the inorganic solid electrolyte evenly distributed in the entire coating can also give the thermally safe coated diaphragm good ionic conductivity.

[0007] Optionally, the above-mentioned phase change material can specifically be at least one of an inorganic phase change material and an organic phase change material; among which, the inorganic phase change materials mainly include crystalline hydrated salts, molten salts, metals or alloys, etc., and the organic phase change materials mainly include paraffin, carboxylic acid, fatty alcohol, polyol and polymer phase change materials, etc.

[0008] Optionally, the above-mentioned diaphragm matrix can be specifically one of PE microporous membrane, PP microporous membrane, PP / PE / PP three-layer composite microporous membrane or non-woven fabric diaphragm. In addition, the total mass proportion of the inorganic solid electrolyte and the phase change material in the above-mentioned bottom layer is preferably greater than or equal to 60%, more preferably 65% ​​to 75%; the total mass proportion of the inorganic solid electrolyte and the phase change material in the surface layer is preferably greater than or equal to 70%, more preferably 75% to 80%.

[0009] As a preferred embodiment of the thermal safety coated diaphragm of the present invention, the surface layer has a multi-layer structure and the mass content of the phase change material in the surface layer is distributed in a gradient decreasing manner along the vertical direction of the surface layer close to the bottom layer. When the surface layer includes multiple layers and the mass content of the phase change material in each layer is distributed in a gradient, the phase change material in the surface layer can be distributed more evenly, thereby better absorbing the heat diffused from the thermal control point to the surroundings to reduce the heat transfer to the diaphragm matrix; at the same time, the inorganic solid electrolyte with a gradient distribution in the surface layer is also conducive to improving the ionic conductivity of the thermal safety coated diaphragm.

[0010] As a preferred embodiment of the thermal safety coated diaphragm of the present invention, the mass content of the phase change material in the bottom layer is less than the mass content of the phase change material in the layer in contact with the bottom layer in the surface layer. When the surface layer has a multilayer structure and the mass content of the phase change material in the layer in contact with the bottom layer is greater than the mass content of the phase change material in the bottom layer, the phase change material in the entire coating can be distributed in a gradient, thereby better absorbing and delaying the transfer and diffusion of heat, thereby greatly extending the time of thermal runaway and significantly improving the safety performance of the battery.

[0011] As a preferred embodiment of the thermal safety coated diaphragm of the present invention, the average thickness of the bottom layer is 0.1-5 μm; and / or the average thickness of the surface layer is 0.1-5 μm. Optionally, the average thickness of the bottom layer in the coating can be 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, and the average thickness of the surface layer can be 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm.

[0012] As a preferred embodiment of the thermal safety coated diaphragm of the present invention, the mass proportion of the phase change material in the bottom layer is ≤35%; and / or the mass proportion of the phase change material in the surface layer is ≥45%. Optionally, the mass proportion of the phase change material in the bottom layer can be 5%, 10%, 15%, 20%, 25%, 30%, preferably 10% to 30%; the mass proportion of the phase change material in the surface layer can be 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%.

[0013] As a preferred embodiment of the thermally safe coated diaphragm of the present invention, the inorganic solid electrolytes in the bottom layer and the surface layer are independently selected from at least one of garnet-type solid electrolytes, perovskite-type solid electrolytes, NASICON-type solid electrolytes, halide electrolytes, and sulfide electrolytes.

[0014] Optionally, the chemical formula of the garnet-type solid electrolyte is Li 7-x Ln3Z 2-x M x O 12 , where M is one of Ta, Nb, Hf, Al, Si, Ga, Ge, Sc, Ti, V, Y and Sn; the general chemical formula of the perovskite solid electrolyte is Li 3x La 2 / 3-x TiO3, wherein x = 0.1 to 0.15; the chemical formula of the NASICON solid electrolyte is LiM(PO4)3, wherein M is selected from Na + , Nb 5+ 、5 + 、Ti 4+ ,Ge 4+ 、Zr 4+ Sn 4+ , Nb 4+ , Hf 4+ 、Al 3+ Cr 3+ , Ga 3+ , Fe 3+ Sc 3+ 、In + , Y 3+ ,La 3+ Mg 2+ 、Zn 2+ , Cu 2+ 、Co 2 + , Mn 2+ , Fe 2+ At least one of; the chemical formula of the halide electrolyte is Li a MX b , where M represents a metal element and X represents a halogen element; the general chemical formula of the sulfide electrolyte is Li 4-x A 1-y B y S4, wherein A may be Si or Ge, and B may be at least one of Zn, Al or P.

[0015] As a preferred embodiment of the thermal safety coated diaphragm of the present invention, the phase change materials in the bottom layer and the surface layer are independently selected from at least one of stearic acid, paraffin, n-dodecanol, n-octadecane, strontium titanate, and manganese dioxide.

[0016] As a preferred embodiment of the heat-safety coated diaphragm of the present invention, the components of the bottom layer and the surface layer also include a binder, a dispersant, a wetting agent and a thickener.

[0017] Optionally, the binder includes one or more of styrene-butadiene latex, styrene-acrylic latex, polybutyl methacrylate, polyacrylate, and polymethyl methacrylate; the dispersant includes one or more of ammonium polyacrylate, sodium polyacrylate, polyacrylamide, polycarboxylate, polyvinyl alcohol, silicate colloid, and propylene glycol block polyether; the wetting agent includes one or more of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium butylnaphthalene sulfonate, and sodium isopropylnaphthalene sulfonate; the thickener includes one or more of sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, hydroxyethyl cellulose, and polyvinyl alcohol-polyacrylic acid copolymer.

[0018] In a second aspect, the present invention provides a method for preparing the above-mentioned thermal safety coated diaphragm, comprising the following steps:

[0019] S1, uniformly mixing the components in the bottom layer and the solvent (water, NMP or DMAC) to obtain coating slurry I, and uniformly mixing the components in the surface layer and the solvent (water, NMP or DMAC) to obtain coating slurry II;

[0020] S2, uniformly coating the coating slurry I described in S1 on the surface of the diaphragm substrate, and forming a bottom layer on the surface of the diaphragm substrate after drying;

[0021] S3. Evenly apply the coating slurry II described in S1 to the surface of the bottom layer described in S2, and obtain a heat-safe coated diaphragm after drying.

[0022] In a third aspect, the present invention provides a use of the above-mentioned thermal safety coated separator in a battery or a capacitor.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The present invention uses a bottom layer and a surface layer mainly composed of an inorganic solid electrolyte and a phase change material as the coating of the diaphragm to form a thermally safe coated diaphragm, and regulates the content of the phase change material in the bottom layer and the surface layer, so that when the battery cell has thermal runaway, the surface layer close to the electrode side and containing a large amount of phase change material quickly absorbs the heat diffused from the runaway point (heat source), so as to reduce and slow down the diffusion of heat to the diaphragm matrix, and effectively alleviate the side reactions and decomposition of the electrolyte and auxiliary materials; while the bottom layer in contact with the diaphragm matrix and containing a small amount of phase change material can use the inorganic solid electrolyte with good heat resistance to fully inhibit the thermal shrinkage of the diaphragm matrix, and use a small amount of phase change material to further absorb the heat transferred from the surface layer, so that the bottom layer and the surface layer work together to reduce the temperature rise rate from T1 (thermal instability temperature, starting point of heat generation) to T2 (thermal runaway trigger temperature), prolong the thermal runaway time, and improve the safety performance of the battery; at the same time, the inorganic solid electrolyte evenly distributed in the entire coating can also give the thermally safe coated diaphragm good ionic conductivity. DETAILED DESCRIPTION

[0025] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.

[0026] Unless otherwise specified, other materials, reagents, etc. used in the examples can be obtained from commercial sources.

[0027] Example 1

[0028] An embodiment of the thermal safety coated diaphragm of the present invention, a method for preparing the thermal safety coated diaphragm of this embodiment comprises the following steps:

[0029] S1, the mixed material A (composed of inorganic solid electrolyte LATP (Li1.3 Al 0.3 Ti 1.7 (PO4)3) and phase change material (stearic acid) in a mass ratio of 9:1), deionized water, dispersant (polyvinyl alcohol), thickener (sodium carboxymethyl cellulose), binder (polyacrylate) and wetting agent (sodium dodecylbenzene sulfonate) in a mass ratio of 45:40:6:3:3:3 are mixed uniformly to obtain coating slurry I;

[0030] S2, mixing mixed material B (composed of inorganic solid electrolyte LATP and phase change material stearic acid in a mass ratio of 5:5), deionized water, dispersant (polyvinyl alcohol), thickener (sodium carboxymethyl cellulose), binder (polyacrylate) and wetting agent (sodium dodecylbenzene sulfonate) in a mass ratio of 45:40:6:3:3:3 to obtain coating slurry II;

[0031] S3, uniformly coating the coating slurry I described in S1 on the surface of the diaphragm substrate (PE diaphragm) (double-sided coating), and forming a bottom layer on the surface of the diaphragm substrate after drying (the average thickness of the bottom layer is 1 μm);

[0032] S4. Uniformly apply the coating slurry II described in S2 to the surface of the bottom layer described in S3, and obtain a thermally safe coated diaphragm (wherein the average thickness of the surface layer is 1 μm) after drying.

[0033] Example 2

[0034] An embodiment of the thermally safe coated diaphragm of the present invention. The preparation method of the thermally safe coated diaphragm described in this embodiment is basically the same as that of Example 1, except that the mixed material B in step S2 is composed of an inorganic solid electrolyte (LATP) and a phase change material (stearic acid) in a mass ratio of 3:7.

[0035] Example 3

[0036] An embodiment of the thermally safe coated diaphragm of the present invention. The preparation method of the thermally safe coated diaphragm described in this embodiment is basically the same as that of Example 1, except that the mixed material B in step S2 is composed of an inorganic solid electrolyte (LATP) and a phase change material (stearic acid) in a mass ratio of 1:9.

[0037] Example 4

[0038] An embodiment of the thermally safe coated diaphragm of the present invention, the preparation method of the thermally safe coated diaphragm described in this embodiment is basically the same as that of Example 1, except that the mixed material A in step S1 is composed of an inorganic solid electrolyte (LATP) and a phase change material (stearic acid) in a mass ratio of 7:3.

[0039] Example 5

[0040] An embodiment of the thermal safety coated diaphragm of the present invention. The preparation method of the thermal safety coated diaphragm in this embodiment is basically the same as that in Example 1, except that the mixed material A in step S1 consists of the inorganic solid electrolyte LATP and the phase change material stearic acid in a mass ratio of 9:1; the mixed material B in step S2 consists of the inorganic solid electrolyte LAGP and the phase change material paraffin in a mass ratio of 5:5.

[0041] Comparative Example 1

[0042] A comparative example of the thermal safety coated diaphragm of the present invention, the preparation method of the thermal safety coated diaphragm of this comparative example comprises the following steps:

[0043] S1. Mix an inorganic solid electrolyte (LATP), deionized water, a dispersant (polyvinyl alcohol), a thickener (sodium carboxymethyl cellulose), a binder (polyacrylate) and a wetting agent (sodium dodecylbenzene sulfonate) in a mass ratio of 45:40:6:3:3:3 to obtain a coating slurry;

[0044] S2. The coating slurry described in S1 is uniformly applied to the surface of the diaphragm substrate (PE diaphragm) (double-sided coating), and after drying, the diaphragm is thermally coated (wherein the average thickness of the coating is 2 μm).

[0045] Comparative Example 2

[0046] A comparative example of the thermal safety coated diaphragm of the present invention, the preparation method of the thermal safety coated diaphragm of this comparative example comprises the following steps:

[0047] S1. Mix the phase change material (stearic acid), deionized water, dispersant (polyvinyl alcohol), thickener (sodium carboxymethyl cellulose), binder (polyacrylate) and wetting agent (sodium dodecylbenzene sulfonate) in a mass ratio of 45:40:6:3:3:3 to obtain a coating slurry;

[0048] S2. The coating slurry described in S1 is uniformly applied to the surface of the diaphragm substrate (PE diaphragm) (double-sided coating), and after drying, the diaphragm is thermally coated (wherein the average thickness of the coating is 2 μm).

[0049] Comparative Example 3

[0050] A comparative example of the thermal safety coated diaphragm of the present invention, the preparation method of the thermal safety coated diaphragm of this comparative example comprises the following steps:

[0051] S1. Mix a mixed material (composed of an inorganic solid electrolyte (LATP) and a phase change material (stearic acid) in a mass ratio of 5:5), deionized water, a dispersant (polyvinyl alcohol), a thickener (sodium carboxymethyl cellulose), a binder (polyacrylate) and a wetting agent (sodium dodecylbenzene sulfonate) in a mass ratio of 45:40:6:3:3:3 to obtain a coating slurry;

[0052] S2. The coating slurry described in S1 is uniformly coated on the surface of the diaphragm substrate (PE diaphragm) (double-sided coating), and after drying, a heat-safe coated diaphragm (wherein the average thickness of the coating is 2 μm) is obtained.

[0053] Performance Testing

[0054] The thermal safety coated diaphragm in each embodiment and comparative example is stacked in order with the positive electrode sheet and the negative electrode sheet, so that the thermal safety coated diaphragm is located between the positive and negative electrode sheets, and a bare battery cell is obtained by winding, shaping, and welding the tabs; then the bare battery cell is placed in a die-stamped housing, and an electrolyte (1M LiPF6 solution, the solvent is prepared by ethyl methyl carbonate (EMC) and ethylene carbonate (EC) in a volume ratio of 1:1) is injected, and the battery cell to be tested is obtained by packaging, standing, forming, and volume separation;

[0055] The preparation method of the positive electrode sheet and the negative electrode sheet is as follows:

[0056] 1) Positive electrode

[0057] S1. The positive electrode active material (NCM532), the conductive agent (conductive carbon black), the dispersant (polyethylene glycol), and the binder (polyvinylidene fluoride) were weighed in a mass ratio of 7:1:1:1, and then NMP was added and mixed and stirred to obtain a positive electrode slurry;

[0058] S2. The positive electrode slurry described in S1 is uniformly coated on the surface of the positive electrode collector (aluminum foil) (double-sided coating), and after drying, it is cold pressed and cut to obtain a positive electrode sheet.

[0059] 2) Negative electrode

[0060] S1. The negative electrode active material (silicon carbon), the conductive agent (conductive carbon black), the binder (styrene-butadiene rubber (SBR)), and the thickener (sodium carboxymethyl cellulose) are mixed in a mass ratio of 7:1:1.5:0.5, and then deionized water is added and mixed and stirred to obtain a negative electrode slurry;

[0061] S2. The negative electrode slurry described in S1 is uniformly coated on the surface of the negative electrode collector (copper foil) (double-sided coating), and after drying, it is cold pressed and cut to obtain a negative electrode sheet.

[0062] The above-mentioned battery cells to be tested were subjected to a needle puncture test, and the ionic conductivity of the thermal safety coated separator was measured. The specific test method is as follows, and the test results are shown in Table 1.

[0063] 1) Puncture test: Place the battery cell to be tested in the puncture test equipment, use a 5mm diameter steel needle (the needle tip is conical and the angle is 30°) to pierce the battery cell at a speed of 25mm / s in the direction perpendicular to the electrode, and observe the battery cell status (whether it is smoking, catching fire, or exploding).

[0064] 2) Ionic conductivity: The thermal safety coated diaphragm in each embodiment and comparative example was sandwiched between two circular steel sheets to assemble into a button cell, and its impedance value was measured using an electrochemical workstation, and the ionic conductivity (σ) was calculated using the following formula;

[0065] σ=d / (R×S), where d is the thickness of the thermal safety coated diaphragm, in cm; R is the body resistance of the thermal safety coated diaphragm, in Ω; S is the contact area between the thermal safety coated diaphragm and the steel sheet, in cm 2 .

[0066] Table 1 Performance of thermal safety coated diaphragms in various embodiments and comparative examples

[0067]

[0068]

[0069] According to the data in Table 1, the ignition time of the battery cells in Examples 1 to 5 is greater than or equal to 4 seconds, and the ionic conductivity is 2.39×10 -4 S / cm or more, indicating that the thermal safety coated diaphragm of the present invention has good ionic conductivity and can effectively prolong the thermal runaway time and improve the safety performance of the battery. At the same time, according to Comparative Examples 1 and 2, it can be seen that the coating with an inorganic solid electrolyte layer as a diaphragm cannot effectively prolong the thermal runaway time; and the coating with a phase change material layer as a diaphragm, although it can significantly prolong the thermal runaway time, it will also cause a decrease in ionic conductivity. In addition, according to Comparative Example 3, it can be seen that directly using an inorganic solid electrode and a phase change material as a diaphragm coating can also improve the thermal runaway time, but the improvement effect is limited.

[0070] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A thermally safe coated diaphragm, characterized in that: It includes a diaphragm substrate and a coating arranged on at least one side of the diaphragm substrate; the coating includes a bottom layer in contact with the diaphragm substrate and a surface layer covering the bottom layer; the bottom layer and the surface layer are mainly composed of an inorganic solid electrolyte and a phase change material, and the mass proportion of the phase change material in the bottom layer is less than its mass proportion in the surface layer.

2. The thermally safe coated diaphragm according to claim 1, characterized in that The surface layer has a multi-layer structure and the mass content of the phase change material in the surface layer is distributed in a gradient decreasing manner along the vertical direction of the surface layer close to the bottom layer.

3. The thermally safe coated diaphragm according to claim 2, characterized in that The mass content of the phase change material in the bottom layer is less than the mass content of the phase change material in the layer in contact with the bottom layer in the surface layer.

4. The thermally safe coated diaphragm according to claim 1, characterized in that The average thickness of the bottom layer is 0.1 to 5 μm; And / or, the average thickness of the surface layer is 0.1-5 μm.

5. The thermally safe coated diaphragm according to claim 1, characterized in that The mass proportion of the phase change material in the bottom layer is ≤35%; And / or, the mass proportion of the phase change material in the surface layer is ≥45%.

6. The thermally safe coated diaphragm according to claim 1, characterized in that The inorganic solid electrolyte in the bottom layer and the surface layer is independently selected from at least one of a garnet-type solid electrolyte, a perovskite-type solid electrolyte, a NASICON-type solid electrolyte, a halide electrolyte, and a sulfide electrolyte.

7. The thermally safe coated diaphragm according to claim 1, characterized in that The phase change materials in the bottom layer and the surface layer are independently selected from at least one of stearic acid, paraffin, n-dodecanol, n-octadecane, strontium titanate and manganese dioxide.

8. The thermally safe coated diaphragm according to claim 1, characterized in that The components of the bottom layer and the surface layer also include a binder, a dispersant, a wetting agent and a thickener.

9. The method for preparing the thermally safe coated diaphragm according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1, uniformly mixing the components in the bottom layer and the solvent to obtain coating slurry I, and uniformly mixing the components in the surface layer and the solvent to obtain coating slurry II; S2, uniformly coating the coating slurry I described in S1 on the surface of the diaphragm substrate, and forming a bottom layer on the surface of the diaphragm substrate after drying; S3. Evenly apply the coating slurry II described in S1 to the surface of the bottom layer described in S2, and obtain a heat-safe coated diaphragm after drying.

10. Use of the thermally safe coated separator according to any one of claims 1 to 8 in batteries or capacitors.

Citation Information

Patent Citations

  • Nano-engineered coatings for anode active materials, cathode active materials, and solid-state electrolytes and methods of making batteries containing nano-engineered coatings

    CN107851840A

  • Composite ceramic particles as well as preparation method and application thereof

    CN113278310A

  • Lithium ion battery diaphragm, and preparation method and application thereof

    CN113745751A

  • Lithium ion battery capable of blocking thermal runaway stage by stage and preparation method of lithium ion battery

    CN115939516A

  • Phase change composite material coated diaphragm and preparation method thereof

    CN117117428A